2022
DOI: 10.1103/physrevb.106.224110
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven motion of charged domain walls in isolated ferroelectrics

Abstract: Light-induced ferroelectric domain wall motion turns out to be a promising phenomenon to develop new photo-controlled devices. However, the physical origin of this ligh-matter coupling when material is irradiated with visible light remains unclear. Here, a phenomenological model predicting the motion of charged domain walls (CDWs) is developed. The photo-induced electronic reconstruction mechanism is proposed as the primary absorption mechanism, leading to a linear dependence for the polarization perturbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…The investigation is prompted by our prior exploration of visible-light-induced deformation in BaTiO 3 , which demonstrated the feasibility of controlling the strain by visible light in a ferroelectric crystal. 7 , 8 , 46 Here, we observe a remarkable macroscopic elongation of approximately 300 nm along the Y -direction ( Figure 4 a), accompanied by a contraction of about 200 nm in the X -direction ( Figure 4 b). In relative terms, the photostrain along the Y -axis is +0.006%, while the contraction along the X -axis is −0.004%.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The investigation is prompted by our prior exploration of visible-light-induced deformation in BaTiO 3 , which demonstrated the feasibility of controlling the strain by visible light in a ferroelectric crystal. 7 , 8 , 46 Here, we observe a remarkable macroscopic elongation of approximately 300 nm along the Y -direction ( Figure 4 a), accompanied by a contraction of about 200 nm in the X -direction ( Figure 4 b). In relative terms, the photostrain along the Y -axis is +0.006%, while the contraction along the X -axis is −0.004%.…”
Section: Resultsmentioning
confidence: 71%
“…As a consequence of these electric fields, ferroelectric domain movements lead to local electric polarization and atomic displacements that are induced at the interface. ,,, The magnetoelectric effect, specifically the converse, involves a variation of magnetization ( M ) due to the application of an electric field ( E ) according to the relation Δ M = α C ·Δ E , where α C represents the magnetoelectric coupling coefficient. Studies have demonstrated significant modifications in the magnetic properties of multiferroic structures with the application of an electric field, including M s modulations of up to 10%. ,, In our case, the incidence of light modifies the domain wall compensation such that the depolarization field inside each domain changes, thereby triggering the domain wall motion . Likewise, the charge-mediated mechanism is claimed to generate an electric polarization at the interface that leads to changes in the oxidation and spin state of the Fe cations, which are responsible for the variations in M s . , To verify this, we conducted XPS measurements on the Fe 2p core level to identify potential electronic variations in the Fe 2+ and Fe 3+ populations on the surface.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The light-driven domain wall motion has been postulated as the main mechanism for the control of strain in BTO. 21,24 In the particular case of the here studied FeAl/BTO heterostructure, the highly oriented domain structure of BTO gives rise to a strong anisotropic strain (Fig. 2a and b) that is responsible for optical modulation of the magnetic properties of the Fe 75 Al 25 film.…”
Section: Resultsmentioning
confidence: 92%
“…The visible-light-induced deformation of the FeAl/BTO heterostructure is explored as a first step to evidence that a strain-mediated light-control of magnetic properties is possible in this engineered magnetostrictive-ferroelectric heterostructure. Since the light-induced macroscopic strain in BTO originates mainly from the light-driven motion of the domain walls, 18,24 an anisotropic strain should be expected. Results show a significant macroscopic elongation of ∼270 nm in the direction perpendicular to the domain walls arrangement upon light illumination (Fig.…”
Section: Resultsmentioning
confidence: 99%